Microbiota as a new pathogenetic factor in the development of chronic hyperuricemia and gout. Part I: the current state of the problem - M. S. Eliseev; E. N. Kharlamova; O. V. Zhelyabina; A. M. Lila (Современная ревматология)
The gut microbiota plays a key role in metabolism and immune regulation, and imbalance in microbial composition can contribute to various diseases. We present up-to-date data on the role of the gut microbiota in the occurrence of chronic hyperuricemia (HU) and gout, which is associated with the influence of the microbiota on the synthesis of purine-metabolizing enzymes and pro-inflammatory cytokines. It has been shown that the gut microbiota plays an important role in the pathophysiology of gout and can serve as a new target for therapy. Currently, the microbial index of gout is considered as a potential method for early diagnosis of the disease, possibly already at the preclinical stage. The gut microbiota can be a starting point in the study of the pathogenesis of HU and gout. This makes it necessary to assess the pathogenetic relationship between individual specific microorganisms, the microbiota as a whole, and the development of uric acid (UA) metabolism disorders that contribute to the onset of HU and its transformation into gout. It is assumed that this approach will provide a more complete understanding of the gut microbiota participation in the synthesis of UA and its extrarenal excretion, as well as of bacteria and bacterial enzymes that can be used as a probiotic coadjuvant for the treatment and prevention of gout.